PENGARUH KUALITAS PELAYANAN FISKUS DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA KARAWANG UTARA - Susanti, Yunita; Suhono, Suhono (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.11.TAHUN 2020, 2020)
This study aims to determine the effect of the quality of tax services and tax sanctions on individual taxpayer compliance at KPP Pratama Karawang Utara. Hypothesis testing in this study was conducted using Multiple Linear Regression Analysis. This research was conducted at KPP Pratama Karawang Utara. The study population was 273,322 individual taxpayers. The sampling technique used was purposive sampling, the determination of the number of samples was carried out using the Slovin formula, in order to obtain the number of respondents as many as 100 individual taxpayers. The results of the research partially and simultaneously show that the Quality of Fiscal Service and Tax Sanctions have a positive and significant effect on Individual Taxpayer Compliance.   Keywords : Fiscus Service Quality; Tax Sanction; Taxpayer Compliance